Erased: The impact of FOSTA-SESTA and the removal of Backpage on sex workers - Blunt, Danielle; Wolf, Ariel (Anti-Trafficking Review, 2020)
This short article presents in brief the findings of a community-based, sex worker-led survey that asked sex workers about their experiences since the closure of Backpage and adoption of FOSTA. It shows that the financial situation of the vast majority of research participants has deteriorated, as has their ability to access community and screen clients. It concludes that FOSTA is just the latest example of the US government using anti-trafficking policy and restrictions on technology to police already marginalised people.